Pelatihan Manajemen Konflik dan Pengelolaan SDM KPU Kabupaten Kebumen - Wiwoho, Gunarso; Dani Rizana (JCSE: Journal of Community Service and Empowerment, 2025)
This Community Service Program was carried out to enhance the capacity, capability, and coordination of the District Election Committee (PPK) under the General Elections Commission (KPU) of Kebumen Regency. Given the strategic role of PPK in ensuring the smooth and credible administration of elections, a solid understanding of conflict management and human resource management is essential. The training activities were conducted through interactive lectures, group discussions, case studies, and conflict-resolution simulations. The results indicate a significant improvement in participants’ understanding of conflict identification, mitigation strategies, and resolution techniques, as well as effective human resource management within the electoral administration context. Participants also demonstrated enhanced abilities in coordination and collaboration across work units. This program contributes meaningfully to strengthening the professionalism and readiness of PPK members in performing their duties at the district level.